JavaScript for beginning web developers - Stone River eLearning; Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"JavaScript is one of the most popular programming languages in the world because it's easy to learn, and it can do amazing things. If you're interested in web development, it's also a language that you simply must learn to be effective."--Resource description page.
Title from resource description page (viewed January 28, 2015)
Date of publication taken from resource description page.
Keywords: JavaScript (Computer program language); Web site development; Scripting languages (Computer science); Electronic books